2014
DOI: 10.1002/jlcr.3212
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic methodologies in organic chemistry involving incorporation of [17O] and [18O] isotopes

Abstract: This review is a critical survey of the literature that aims to highlight the most significant developments on synthetic strategies involving stable oxygen isotopes ([(17)O] and [(18)O]). The labeling methodologies are categorized in groups, according to the oxygen-containing functional group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 225 publications
(278 reference statements)
0
13
0
Order By: Relevance
“…[62][63] These conditions prohibit acidcatalyzed exchange to be used for 17 O enrichment in protected amino acids or proteins, and therefore we have turned to an alternative procedure utilizing mild conditions and yielding 17 O/ 18 O isotopic enrichment efficiencies of >95%. 46,59,[62][63][64] Utilizing this approach, illustrated in The following reagents were purchased from Sigma Aldrich (St. Louis, MO), 1-ethyl-3-(3-dimethylaminopropyl)carboiimide hydrochloride (EDC • HCl), dimethylformamide (kept in a septum container), and 3,5-dimethylpyridine, which was then reacted with HBr (33% in acetic acid) to form 3,5-dimethylpyridine • HBr that was lyophilized to remove residual water. All Peptide, N-Ac-VL).…”
Section: Materials and Synthesismentioning
confidence: 99%
“…[62][63] These conditions prohibit acidcatalyzed exchange to be used for 17 O enrichment in protected amino acids or proteins, and therefore we have turned to an alternative procedure utilizing mild conditions and yielding 17 O/ 18 O isotopic enrichment efficiencies of >95%. 46,59,[62][63][64] Utilizing this approach, illustrated in The following reagents were purchased from Sigma Aldrich (St. Louis, MO), 1-ethyl-3-(3-dimethylaminopropyl)carboiimide hydrochloride (EDC • HCl), dimethylformamide (kept in a septum container), and 3,5-dimethylpyridine, which was then reacted with HBr (33% in acetic acid) to form 3,5-dimethylpyridine • HBr that was lyophilized to remove residual water. All Peptide, N-Ac-VL).…”
Section: Materials and Synthesismentioning
confidence: 99%
“…The most common approach to improving the sensitivity of 17 O NMR experiments is isotopic enrichment of oxygen-17, for which a variety of methods have been successfully demonstrated. 3,[27][28][29][30][31] More recently, it has been demonstrated that with the large NMR sensitivity enhancements provided by high-field dynamic nuclear polarization (DNP), [32][33][34] natural isotopic abundance 17 O NMR experiments can be performed on inorganic materials. 19, 23-24, 26, 35-36 The resolution of 17 O SSNMR spectra is most often improved either by utilizing selective 17 O labeling schemes, 37 working at the highest possible magnetic field strengths, 12,25,[38][39] or using multiple quantum magic angle spinning (MQMAS).…”
Section: Introductionmentioning
confidence: 99%
“…al. [19]. (TBDMS-Cl = tert -butyldimethylsilyl chloride; TMEDA = tetramethylethylenediamine, DMF = dimethylformamide)…”
Section: Highlightsmentioning
confidence: 99%
“…Moreover, we highlight only state-of-the-art syntheses for these substrates with an emphasis on methodologies that generate substrates isotopically enriched at a single atomic position. Interested readers should also consult excellent reviews by Theodorou et al [19] and Milecki [20], which contain a more complete account of isotopically labeled nucleotides.…”
Section: Introductionmentioning
confidence: 99%